P655GRK2 subcellular localization in response to radiation stress in cardiac myocytes. (15th July 2014) - Franco, A; Annunziata, R; Pacelli, R; Prevete, N; Trimarco, B; Sorriento, D; Iaccarino, G; Ciccarelli, M
Abstract: GRK2 is an ubiquitous 80kd protein that interacts with several molecular partners in different cellular compartments. Recent studies have shown in endothelial cells that GRK2 localizes within the mitochondria, improves biogenesis and protects from ATP loss in response to ischemia/reperfusion. To evaluate cellular trafficking of GRK2 in isolated adult ventricular cardiomyocytes (AVM) from C57BL6 mice under stress condition, we isolated and cultured AVM, exposed them to 4Gy by Isovolt DS-1x-ray tube (Seifer), and subjected to differential centrifugation to isolate mitochondria, plasma membranes and cytosol fractions. GRK2 subcellular localization was evaluated by western blot at 3 and 8 hours from ionizing radiation exposure. At 3 hours from irradiation GRK2 is mainly localized in membranes, and its level are reduced in mitochondria. At 8 hours from irradiation, GRK2 accumulates into mitochondrial. Giving the role of GRK2 in the regulation of mitochondrial function we analyzed the production of reactive oxygen species (ROS) with DCHF (10-3M) and mitochondrial mass by Mito Traker (5nM) at 3 and 8 hours after irradiation. We found no modification in ROS production but reduction in mitochondrial mass after 3 hours from irradiation. After 8 hours, ROS production was increased along with mitochondrial mass. These date suggest that GRK2 subcellular localization is regulated in a time dependent manner in response to irradiation stress and it is associated with relevant modification of mitochondrial function. In conclusion, the regulation of GRK2 subcellular localization appears pivotal for the regulation of cardiomyocytes mitochondrial function in stress condition.